Own goals in football: do they occur randomly or exhibit systematic patterns? - Mehta, S.; Schlenger, J.; Memmert, D.; Wunderlich, F. (International Journal of Performance Analysis in Sport, 2025)
Due to the low-scoring nature of soccer every single goal can drastically change the outcome of a match. Therefore, most large-scale performance studies aim at defining systematic processes and factors involved in goal scoring, while the scoring of the seemingly unintentional goals (like own goals) appears to be overlooked so far. In this study, factors for scoring own goals are investigated and compared to the factors connected to other (normal) goals. Therefore, a large dataset consisting of all goals from seven full seasons of the English Premier League (seasons 12/13 to 18/19) was analysed. Factors investigated include a priori factors like matchday, playing minute and team strength, but also specific situational variables like the zone from where the goal was scored, the body parts used, scoreline, defensive order and the preceding action. Favourites (p < .001) and home teams (p <0.05) profit more often from own goals than outsiders and away teams, suggesting systematic influences on own goal scoring. However, own goals significantly differ from all goals in the zone of goal scoring where more than 50% of the own goals are scored from the zone closest to goal (Zone 1). Additional aspects and potential reasons for the observed patterns are discussed.